2017
DOI: 10.1121/1.4974760
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion crack depth investigation using the time reversed elastic nonlinearity diagnostic

Abstract: Evidence of the ability to probe depth information of stress corrosion cracking (SCC) are presented using the time reversed elastic nonlinearity diagnostic (TREND). Depth estimation of SCC is important to determine when a stainless steel canister has been breached. TREND is a method to focus elastic energy to a point in space in order to probe that point for damage and its' depth penetration is used here to study depth information about SCC. High frequencies are used to probe near the surface, while low freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…*4./50,'k-'); end grid; xlabel('Frequency (kHz)','fontsize',18) ylabel('Velocity (mm/s)','fontsize',18) set(gca,'fontsize',16) end hold off eps=zeros(num/2,10); for n=1:1:num/2 for m=1:1:10 eps(n,m) = b(n,m)./5./c(n). *1e6; end end eps(13,:) = eps(13,:)./5; p=zeros(num,2); t=0:2:24; for n=1:1:num/2 p(n,:)=polyfit(eps(n,:),g(n,:),1); yfit(n,:) =polyval(p(n,:),eps(n,:)); yresid(n,:)=g(n,:)-yfit(n,:); SSresid=sum(yresid(n,:).^2); SStotal=(length(g(n,:))-1) * var(g(n,:)); rsq(n)=1-SSresid/SStotal; end for n=1:1:(num/2) pt(n)=p(n,1); fit(n,:)=(p(n,1)*(0:.2:5) + p(n,2)); end figure plot(t,abs(pt)) xlabel('Time (days)','fontsize', 18 ;w=2*pi*P(1,1,n-1); %young(n/2)=m*w*c(n/2)/tan(w*L/c(n/2))/S; rho=8030; young(n/2)=rho*c(n/2).^2; maxf(n/2)=(P(1,1,n-1)-P(1,37,n))/P(1,1,n-1); end…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…*4./50,'k-'); end grid; xlabel('Frequency (kHz)','fontsize',18) ylabel('Velocity (mm/s)','fontsize',18) set(gca,'fontsize',16) end hold off eps=zeros(num/2,10); for n=1:1:num/2 for m=1:1:10 eps(n,m) = b(n,m)./5./c(n). *1e6; end end eps(13,:) = eps(13,:)./5; p=zeros(num,2); t=0:2:24; for n=1:1:num/2 p(n,:)=polyfit(eps(n,:),g(n,:),1); yfit(n,:) =polyval(p(n,:),eps(n,:)); yresid(n,:)=g(n,:)-yfit(n,:); SSresid=sum(yresid(n,:).^2); SStotal=(length(g(n,:))-1) * var(g(n,:)); rsq(n)=1-SSresid/SStotal; end for n=1:1:(num/2) pt(n)=p(n,1); fit(n,:)=(p(n,1)*(0:.2:5) + p(n,2)); end figure plot(t,abs(pt)) xlabel('Time (days)','fontsize', 18 ;w=2*pi*P(1,1,n-1); %young(n/2)=m*w*c(n/2)/tan(w*L/c(n/2))/S; rho=8030; young(n/2)=rho*c(n/2).^2; maxf(n/2)=(P(1,1,n-1)-P(1,37,n))/P(1,1,n-1); end…”
Section: Appendix Amentioning
confidence: 99%
“…Elastic Nonlinearity Diagnostic to explore the depth dependence of SCC near welds. 18 The majority of the nonlinear acoustic techniques were applied to a single sample for proof of concept of the technique's ability to detect SCC rather than being applied to a set of samples with progressive damage.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…3,4 In 2001, Guyer first proposed using high-amplitude TR focusing for nonlinear imaging of cracks, 5 and Ulrich et al demonstrated this experimentally a few years later by locating a surficial crack in a doped glass sample. 6 Studies since then have used TR to find nonlinearity in various types of surface cracks, [7][8][9][10] near-surficial cracks and delaminations, 10,11 and even buried cracks. 10,12 The detection of cracks using nonlinear methods is rooted in the premise that cracks will generate nonlinear frequency mixing when excited with sufficient amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear NDE of cracks and defects using TR is usually accomplished through the detection of a relative increase in harmonics 8,11,32 or sum and difference frequencies 6,7 (i.e., through the introduction of nonlinear frequency content). Some techniques have been developed to detect distortions in the focal signal when the focusing experiment is conducted multiple times.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This early experiment utilized what has been termed reciprocal time reversal (RTR), 2 where a signal is broadcast from location A, a recording of the signal is made at location B, this recording is then flipped in time, sent electronically to location A, subsequently broadcast from location A, and a TR focus is then created at location B. Subsequently, researchers have named the technique time reversal acoustics and have recently applied it to underwater communications, 6,7 medical applications, 8,9 nondestructive evaluation, [10][11][12][13] and infrasound.…”
Section: Introductionmentioning
confidence: 99%